Digital Marketing on Sales Effectiveness and Market Expansion for Msmes: A Literature Review - Alvianno Difta Sunggara; Putri Nurhaliza; Augusty Tae Ferdinand; I Made Bayu Dirgantara (LifeSciFi, 2022)
This literature review explores the impact of digital marketing on the sales effectiveness and market expansion of MSMEs. It examines the role of digital strategies such as Search Engine Optimization (SEO), Pay-Per-Click (PPC), and social media in enhancing the visibility and reach of MSMEs in the digital world. These strategies help MSMEs rank higher on search engines and target specific customer segments, thus improving market access and conversion rates. However, the adoption of digital marketing by MSMEs is challenged by limited technological knowledge and inadequate access to digital infrastructure, especially in rural areas. The review highlights the importance of government and institutional support, including training programs, digital platform access, and financial assistance, to help MSMEs leverage digital technologies effectively. Furthermore, the review discusses how digitalization initiatives, such as ecommerce and digital payment systems, contribute to MSME growth and competitiveness. By synthesizing existing research, this study underscores the synergy between digital marketing strategies and MSME empowerment in fostering long-term business sustainability and economic growth. The findings suggest that overcoming digital adoption challenges with proper support mechanisms can enhance MSMEs' market presence and sales performance in a competitive digital economy.